Analisis Penggunaan Media Video Pembelajaran Pada Mata Pelajaran Seni Budaya - Anugrah Putra, Chandra; Sukmaraga, Aditya (Pedagogik: Jurnal Pendidikan, 2024)
With today's technology, it is elementary for us to learn various things from various media, including videos, and we no longer need to use the old methods completely. This method is one solution to learning problems that we need to follow with the learning concept of today's students who mainly use all technology. The research method used in this research is qualitative research methods. This research aims to determine the use of learning video media in class VII arts and culture at Junior High School 2 Kahayan Hilir. The data collection techniques used in this research are observation, interviews, and documentation. Research data analysis using stages of data collection, data presentation, and conclusions. Learning video media in Arts and Culture subjects has been good. The fulfillment of preparation, implementation, and follow-up indicators proves this. Learning video media is useful as a supporting medium in the learning process, helping teachers provide students with a good understanding of learning material.